2018
DOI: 10.1002/humu.23683
|View full text |Cite
|
Sign up to set email alerts
|

Small supernumerary marker chromosomes: A legacy of trisomy rescue?

Abstract: We studied by a whole genomic approach and trios genotyping, 12 de novo, nonrecurrent small supernumerary marker chromosomes (sSMC), detected as mosaics during pre‐ or postnatal diagnosis and associated with increased maternal age. Four sSMCs contained pericentromeric portions only, whereas eight had additional non‐contiguous portions of the same chromosome, assembled together in a disordered fashion by repair‐based mechanisms in a chromothriptic event. Maternal hetero/isodisomy was detected with a paternal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
(49 reference statements)
0
27
0
2
Order By: Relevance
“…Most sSMCs are caused by a multiple-step mechanism: firstly, maternal meiotic nondisjunction, and then postzygotic anaphase lagging of the SMC and its subsequent chromothripsis [16]. The sSMCs Dup15q is characterized by hypotonia motor delays, autism spectrum disorder (ASD), intellectual disability, and epilepsy including infantile spasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most sSMCs are caused by a multiple-step mechanism: firstly, maternal meiotic nondisjunction, and then postzygotic anaphase lagging of the SMC and its subsequent chromothripsis [16]. The sSMCs Dup15q is characterized by hypotonia motor delays, autism spectrum disorder (ASD), intellectual disability, and epilepsy including infantile spasms.…”
Section: Discussionmentioning
confidence: 99%
“…CNV-Seq showed a 10. 16 this difference may be that the theories are different between these two technologies: SNP array is a microarray-based method while CNV-Seq is based on next-generation sequencing. The number of probes and DNA segments on a microarray does not represent the true copy number of sequences in an assembled genome.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the process of chromothripsis is interrupted, it can cause partial chromosomal loss and/or rearrangements with or without UPD ( Figure 1A) (Liehr, 2010). Co-occurrence of de novo CCRs and UPD, particularly those involving a set of homologous chromosomes, is indicative of incomplete trisomy rescue (Liehr et al, 2011;Kurtas et al, 2019). Previous studies have shown that a substantial proportion of UPD cases were accompanied by additional genomic or cytogenetic abnormalities (Liehr, 2010).…”
Section: Various Chromosomal Rearrangements Can Be Created In Micronumentioning
confidence: 99%
“…Recent studies have suggested that de novo non-recurrent small SMCs result from incomplete trisomy rescue (Kurtas et al, 2019). Trisomy rescue is a physiological phenomenon to eliminate excessive chromosomes from trisomic cells (Fenech et al, 2011;Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation